Assessment of nitric oxide and uric acid in patients of leprosy - Trimbake, Sangeeta B.; Sontakke, Alka N.; Gaikwad, Rohini P. (International Journal of Research in Medical Sciences, 2020)
Background: Leprosy is an old, dreaded infectious disease caused by the obligate intracellular bacterium mycobacterium leprae. Leprosy still continues to be a significant public health problem in few countries including India. Oxidative stress caused by derangement in the balance between ROS and natural antioxidants plays a crucial role in the pathogenesis of leprosy. Hence this study attempts to assess the oxidative stress and antioxidant status in terms of Nitric oxide and uric acid. Methods: A case control observational study was carried out in100 untreated leprosy patients and compared with 50 healthy controls. Leprosy patients were divided as paucibacillary and multibacillary. Serum Nitric oxide and uric acid levels were estimated in both groups to find out correlation of Nitric Oxide with uric acid. Results: There was a significant rise in serum NO in both PB and MB leprosy as compared to controls. The uric acid level was significantly decreased in both PB and MB leprosy patients as compared to controls. Conclusions: Elevated NO levels indicate oxidative stress in leprosy patients, denoting its crucial involvement in the pathogenesis and nerve damage in leprosy. Low uric acid indicates decrease defence of antioxidants in leprosy.